The Acting in Group of Teachers as Possibility of Resignification of the Interpretation about the Writing Language - Giroto, Cláudia Regina Mosca [UNESP]; Castro, Rosane Michelli de [UNESP]; Vitta, Fabiana Cristina Frigieri de [UNESP]; Cicilino, Joice Emanuele Munhoz [UNESP] (Scientific Research Publishing, 2014)
Front of the possibility of acting with the teachers who teach in schools of Early Childhood Education for children aged six years, about the re-siginification of the understanding of writing language and of the importance of the child in this age group establish a positive relationship with this mode of language, was developed in 2011, a project linked to the Teaching of UNESP titled “Depathologization learning of the writing and inclusive education: reflections and actions of the teacher of Early Childhood Education”. This project aims to identification of the actions, in the classroom, of the patologization and subsequent implementation of actions depathologization writing by teachers’ actions, considering the increasingly early systematization of formal education of this kind of language in kindergarten. To this end, procedures that characterize the collaborative methodology are adopted. Throughout the methodological course, the engagement of the teachers, of the coordination and of the direction was valued, which seemed to favor both the formation, as the maintenance of the group, were very important aspects to ensure the interaction between its members and the common interest in the reflection about the topic in question. This paper focuses attention on whether thematic axes highlight during the initial survey of the expectations of teachers subsequently addressed in theoretical and reflective meetings leading up to identification of actions the patologization and/or of the proposition of the actions despatologizadoras of the learning of the writing, and in what refers to the way they are addressed.